2017
DOI: 10.1001/jamaoncol.2016.4365
|View full text |Cite
|
Sign up to set email alerts
|

New Yellow Plaques in a Patient Taking Pembrolizumab

Abstract: A woman in her 70s presented with a new 4-cm left upper lobe lung mass with hilar lymphadenopathy. Biopsy results demonstrated a squamous cell carcinoma (SCC) of the lung, and chemoradiotherapy with carboplatin and paclitaxel for stage 3A disease was initiated. An allergic reaction prompted a change to cisplatin-etoposide, which continued as adjuvant chemotherapy after the radiation was complete. At first restaging, a recurrence of disease in the lung was detected, which was treated with cisplatin and gemcitab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
0
5
0
1
Order By: Relevance
“…In terms of specifically for lichenoid reactions the main management includes topical and systemic corticosteroids [22]. The majority are able to be maintained on their anti-PD1 therapy (81%) and it was concluded that treatment can still be continued [23].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of specifically for lichenoid reactions the main management includes topical and systemic corticosteroids [22]. The majority are able to be maintained on their anti-PD1 therapy (81%) and it was concluded that treatment can still be continued [23].…”
Section: Discussionmentioning
confidence: 99%
“…The consistency of the clinical findings with HLP in the setting of ICB therapy led to the use of topical steroids as appropriate treatment for this condition, with complete resolution of the cutaneous lesions in both patients (Table 1). ICB therapy is associated with irAEs, such as dermatologic toxicities [5][6][7], caused by possible antigen "unmasking" in which PD-1 pathway blockade allows for the body to mount an immune response to the uncovered antigens [8]. Lichenoid reactions observed in the context of anti-PD-1 therapy support the possible role of the PD-1 pathway in lichen planus [6,7,9].…”
Section: Discussionmentioning
confidence: 99%
“…ICB therapy is associated with irAEs, such as dermatologic toxicities [5][6][7], caused by possible antigen "unmasking" in which PD-1 pathway blockade allows for the body to mount an immune response to the uncovered antigens [8]. Lichenoid reactions observed in the context of anti-PD-1 therapy support the possible role of the PD-1 pathway in lichen planus [6,7,9]. One study of approximately 80 patients receiving either pembrolizumab or nivolumab noted a lichenoid eruption in nearly one-fifth of patients [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations